The Effect of Celebrity Endorsement on Consumer Buying Behaviour: An Applied Study on the Real Estate Market in Egypt - Kamal, Nitsa Sherif (Archives of Business Research, 2024)
Marketers believe that the use of celebrities is important in order to gain customers’ attention and make customers interested in buying real estate or any product. That is why nowadays, companies spend huge amounts of money for the use of celebrity endorsements in the marketing of products. In fact, Celebrity Endorsement is viewed as a billion dollar industry in today’s era” (Giridhar, 2012) While, a celebrity is someone who is famous and known for certain characteristics that people usually identity with, the act of endorsement is actually considered the communication channel in which a certain celebrity is paid for in order to become the “spokesperson” of a brand and assure the brand’s position (Zipporah, 2014). Endorsing a celebrity have been used extensively that customers often remember the product just because their favorite celebrity endorsed it. Different multinational companies in Egypt are having their own market intelligence and product research; based on which they can determine whether or not to endorse a celebrity in their advertisements and other promotional activities. However, no scientific research studies have been conducted in Egypt to highlight the factors that might strongly affect the product acceptance or intention of buying by Egyptian consumers, on real estate buyers in particular. Moreover, no scientific research studies were conducted to identify the extent to which using celebrities would strongly convince people of buying a residential unit for their own personal use or for investment . This study ventures to close the above gaps; however, the focus of the study will be on the real estate market. The study will be conducted on this field in particular because developers, using good-looking celebrities that portray this perfect looking lifestyle in a compound to market their projects, is raising the curiosity of whether Egyptian customers are truly affected by those celebrities, and the extent to which it affects their buying intention towards these projects( compounds). This study will also be discussing in depth the variables affecting the characteristics of the celebrity used in marketing by developers on their projects. Research questions followed by the hypothesis will be as follows: Q1: Does the celebrity “credibility” characteristic positively impacts consumer buying behavior in the real estate industry ? H1: The credibility characteristic has no significant effect on home buyers in behavior in the . Q2: whether celebrity endorsements influence positively or negatively consumer buying behaviors in purchasing real estate. H0: celebrity endorsements have no effect on consumer buying behavior. H2: celebrity endorsements strongly influence consumer buying behavior. The objectives of this study are as follows: To identify the strongest dimensions of celebrity endorsement that affects project choice. To identify the factors that should be considered when selecting a celebrity endorser by developers. To determine the degree of impact that celebrity endorsement has on consumer buying intention for projects in the real estate market.